Marginalization of the Youth - a Current Societal Development? - Niels Rosendal Jensen (Social Work and Society)
The last two years a discussion on reforming the public sector has emerged. At its very heart we find important concepts like "˜quality reform', "˜democracy', and "˜development'. Recently I have presented an example of the "˜quality reform' in SocMag, and this leads me to prolong that discussion on central themes on welfare state and democracy. Much energy is invested in arguing about management of the public sector: Do we need more competition from private companies? Do we need more control? Are more contracts concerning outcome needed? Can we be sure about the accountability needed from politicians? How much documentation, effectiveness measurement, bureaucracy, and evidence-based policy and practice are we looking for? A number of interesting questions - but strange enough we do not discuss the purpose of "˜keeping a welfare state'. What sort of understanding is lying behind the welfare state, and what kind of democracy are we drawing upon?